2021
DOI: 10.1055/a-1675-7860
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a treatment response threshold for the Eosinophilic Esophagitis Endoscopic Reference Score

Abstract: Background and study aims: While endoscopic features of eosinophilic esophagitis (EoE) are measured using the validated EoE Endoscopic Reference Score (EREFS), a threshold for treatment response has not been defined. We aimed to determine a cut-point for endoscopic response as measured by EREFS. Patients and Methods: We performed a secondary analysis of a randomized clinical trial comparing budesonide slurry to swallowed fluticasone multidose inhaler for initial treatment of EoE. In the parent trial, EREFS wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
2
10
0
1
Order By: Relevance
“…There was also a significant difference in EDP scores above and below the 15 eos/hpf histologic threshold. Interestingly, the EREFS data had more variability, which is consistent with previous reports that EREFS modestly correlates with histologic involvement (5,6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was also a significant difference in EDP scores above and below the 15 eos/hpf histologic threshold. Interestingly, the EREFS data had more variability, which is consistent with previous reports that EREFS modestly correlates with histologic involvement (5,6).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, EREFS has been shown to validly measure endoscopic severity and improve (decreasing score) with response to EoE treatment (2,4,5). However, posttreatment EREFS response thresholds have only recently been proposed (6). Furthermore, these posttreatment thresholds have never been assessed in the context of molecular changes in EoE.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its value for standardizing reporting of endoscopic severity in both practice and clinical trials, 20,[28][29][30]65,66,94,95 current data do not support using prespecified scores to determine severity. 96 Therefore, a somewhat abbreviated version of the EREFS should be used clinically to assess the endoscopic inflammatory features, defined as edema, furrows, and exudates. In addition, a determination of "localized" vs "diffuse" should be reported.…”
Section: Inflammatory Featuresmentioning
confidence: 99%
“…In the diffuse type with no treatment, endoscopic abnormalities persisted but did not exacerbate in most patients without developing symptoms requiring active treatment. In contrast, in the localized type with no treatment, endoscopic activity remained unchanged or rather improved significantly, with a predominance of patients showing endoscopic remission (defined as total EREFS ≤2) in an earlier phase during follow-up [24]. We previously reported that endoscopic abnormalities remained unchanged in the diffuse type but were significantly improved in the localized type of aEE with no treatment for >3 years (median: 50-60 months) [18].…”
Section: Discussionmentioning
confidence: 93%